2016
DOI: 10.1186/s12864-016-3242-9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics analysis reveals molecular mechanisms of shoot adaption to salt stress in Tibetan wild barley

Abstract: BackgroundTibetan wild barley (Hordeum spontaneum L.) has been confirmed to contain elite accessions in tolerance to abiotic stresses, including salinity. However, molecular mechanisms underlying genotypic difference of salt tolerance in wild barley are unknown.ResultsIn this study, two Tibetan wild barley accessions (XZ26 and XZ169), differing greatly in salt tolerance, were used to determine changes of ionomic, metabolomic and proteomic profiles in the shoots exposed to salt stress at seedling stage. Compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 42 publications
2
43
0
Order By: Relevance
“…A low Na/K ratio is a key feature of plant resistance to salt stress in saline environments [69,70]. In the current study, the Na/K ratios in the leaves and stems were higher than that in the roots, which is similar in Tibetan wild barley under salt stress [62], indicating that maintaining an optimal Na/K ratio could improve salt tolerance. Kirmizi and Bell [71] reported that nutrient element uptake and distribution in plant tissues are affected by salt stress.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…A low Na/K ratio is a key feature of plant resistance to salt stress in saline environments [69,70]. In the current study, the Na/K ratios in the leaves and stems were higher than that in the roots, which is similar in Tibetan wild barley under salt stress [62], indicating that maintaining an optimal Na/K ratio could improve salt tolerance. Kirmizi and Bell [71] reported that nutrient element uptake and distribution in plant tissues are affected by salt stress.…”
Section: Discussionsupporting
confidence: 51%
“…High-throughput omics techniques have been widely used to research complex molecular responses underlying salt tolerance in plants [62], and transcriptome analysis has become an attractive alternative for in-depth research of the salt tolerance molecular mechanism of N. sibirica Pall. Therefore, in order to understand the mechanisms of salt tolerance in N. sibirica Pall., different treatments were used to investigate the molecular and ion content changes in response to salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, narrow genetic diversity in the cultivated barley has become a bottleneck for further genetic improvement [ 10 ]. On the other hand, Tibetan annual wild barley, as one of the ancestors of cultivated barley [ 11 ], is rich in genetic diversity and the elite accessions tolerant to abiotic stresses, such as drought and salinity [ 12 14 ], as well as to poor fertility, including low K [ 15 17 ]. However, the physiological and molecular mechanisms conferring low K tolerance in wild barley remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the multidrug transporter AcrB, a heavy metal cation efflux protein, plays a significant role in salt resistance in Escherichia coli [ 45 ]. According to previous reports [ 46 ], AAA family ATPase contributes to shoot adaption to salt stress in Tibetan wild barley. In addition, previous research on the fungus Ascochyta rabiei found that expression of F-box and WD protein (FBO) and several heat shock proteins was highly induced under oxidative stress [ 47 ].…”
Section: Discussionmentioning
confidence: 99%